Historical trajectory of women's health policies in Angola - Eurica da Natividade Sinclética Graça Neves da Rocha; Driéli Pacheco Rodrigues; Luciana Barizon Luchesi; Maria da Conceição Martins da Silva; Juliana Cristina dos Santos Monteiro (Universidad de Alicante, 2018)
The aim of this study was to describe an historical view of public policies focused on women's health in Angola. This is a historical perspective research, using documental analysis and categorical analysis of official historical sources, from the Ministry of Health and the National Directorate of Public Health of Angola and the official website of the World Health Organization, from 1975 to 2012. The documentary corpus consisted of 12 documents. It was observed that women's health policies are mixed with health policies for the population, formulated with international investments and strongly influenced by the global situation in the period. It was observed difficulties to fully implement the planned actions. It was concluded that despite the efforts made, Angola's challenge continues to be to improve the delivery of women's health care, and to increase access to quality services for the entire population.